Life Cycle Assessment of ammonia vs liquefied natural gas in a sea going shipping vessel. - Zulqarnain (My University, 2026)
The shipping industry across the globe is being put under severe pressure to reduce greenhouse gas (GHG) emissions to ensure that it meets international climate targets. This has led to an increased interest and necessity of alternative marine fuels that can contribute towards decarbonization of the shipping industry. In this context, liquefied natural gas (LNG) and green ammonia are often reported among other alternative marine fuels currently under consideration as a way of decarbonizing the maritime industry. LNG is considered as the transitional fuel whereas ammonia being carbon free is a promising net zero carbon option. The environmental performance of these alternative marine fuels remains uncertain due to the limited availability of life cycle assessment (LCA) studies on these emerging options. The existing LCA studies are limited by their inconsistency and transparency towards methodological choices and assumptions, raising concerns about the reliability of the results. This study aims to compare the environmental performance of LNG and green ammonia with respect to their applicability to the maritime industry in terms of their global warming potential (GWP). A tank to wake (TTW) LCA framework has been used to analyse the emissions related to fuel combustion. The study is conducted on a real offshore supply vessel operating on a selected route with a functional unit of one complete round trip. A transparent Excel based LCA model was developed to calculate the total energy demand, fuel consumption, emissions associated with both configurations and their respective GWP. The results suggest that the comparative climate performance of the two fuels is strongly dependent on pollutant specific emissions as well as emission control assumptions. Emissions from both ammonia and LNG fuel pathways are key drivers of GWP. In the case of ammonia, nitrogen oxides (NOx), nitrous oxide (N₂O), and unburned ammonia (ammonia slip) are particularly significant, while for LNG, carbon dioxide (CO₂) and methane (CH₄) emissions play a dominant role in shaping overall climate impact. Without any emission control measures, ammonia combustion has a higher GWP when compared to LNG, as it is dominated by N2O with a very potent GWP potential. Scenario-based analysis is performed to study the effect of catalytic emission control systems on N2O emissions related to ammonia-fuelled engine systems. The results show that the environmental performance of green ammonia strongly depends on the integration of emissions reduction technology. Even the conservative efficiency of the selective catalytic reduction (SCR) exhibits much lower overall GHG emissions as compared to LNG. Overall, the findings suggest that LNG can serve as a transitional fuel by offering lower emissions compared to conventional marine fuels, whereas green ammonia holds significant long-term potential for maritime decarbonization, provided that nitrogen-related emissions are effectively controlled.
Keywords: emissions; fuels; life cycle analysis; greenhouse gases; environmental effects; Industrial Systems Analytics; Master's Programme in Industrial Systems Analytics